The African principle of reciprocity: Examining the "golden rule" in light of the ubuntu philosophy of life - Mligo, Elia Shabani (Stellenbosch Theological Journal, 2022)
The aspect of reciprocity is highly enshrined in the African culture. It is part and parcel of communal life of African people despite their various life predicaments. However, reciprocity is not only found in African culture; it is also a universal aspect found in other cultures and religions of the world. The universality of reciprocity is evident in the universal golden rule. Through surveying the golden rule in the various religious traditions and examining the tenets of the African philosophy of Ubuntu, this article argues that although reciprocity is a universal aspect, it can hardly be fully realized in Africa without considering the African philosophy of Ubuntu. The philosophy of Ubuntu stands not only as a cornerstone for African reciprocal relationships, but also as a distinction between the African and other ways of life.